PDGFR-β as a positive regulator of tissue repair in a mouse model of focal cerebral ischemia - Shen, Jie (Nature Publishing Group, 2012)
Although platelet-derived growth factors (PDGFs) and receptors (PDGFRs) are abundantly expressed in the central nervous system, their functions largely remain elusive. We investigated the role of PDGFR-β in tissue responses and functional recovery after photothrombolic middle cerebral artery occlusion (MCAO). In the normal adult mouse brain, PDGFR-β was mainly localized in neurons and in pericyte/vascular smooth muscle cells (PC/vSMCs). From 3 to 28 days after MCAO, postnatally induced systemic PDGFR-β knockout mice (Esr-KO) exhibited the delayed recovery of body weight and behavior, and larger infarction volume than controls. In Esr-KO, PC/vSMC coverage was decreased and vascular leakage of infused fluorescent-labeled albumin was extensive within the ischemic lesion, but not in the uninjured cerebral cortex. Angiogenesis levels were comparable between Esr-KO and controls. In another PDGFR-β conditional KO mouse (Nestin-KO), PDGFR-β was deleted in neurons and astrocytes from embryonic day 10.5, but was preserved in PC/vSMCs. After MCAO, vascular leakage and infarction volume in Nestin-KO were worse than controls, but partly improved compared with Esr-KO. Astroglial scar formation in both Esr-KO and Nestin-KO was similarly reduced compared with controls after MCAO. These data suggested that PDGFR-β signaling is crucial for neuroprotection, endogenous tissue repair, and functional recovery after stroke by targeting neurons, PC/vSMCs, and astrocytes.